2010
DOI: 10.2478/s11756-010-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

The protozoan toxin climacostol and its derivatives: Cytotoxicity studies on 10 species of free-living ciliates

Abstract: Climacostol (5-(Z)-non-2-enyl-benzene-1,3-diol) is a natural toxin isolated from the freshwater ciliated protozoan Climacostomum virens and belongs to resorcinolic lipids, a group of compounds that show antimicrobial, antiparasitic, and anticancer activities. We investigated the cytotoxic activity of the chemically synthesized toxin and its alkyl and alkynyl derivatives on C. virens and nine other common species of free-living freshwater ciliates. Our results show that the cytotoxic potency of climacostol can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…), Spirostomum ambiguum stock Pol‐5 (Buonanno et al. ), and Spirostomum teres stock Pol‐1 (Buonanno ) were grown in bacterized culture medium as described in Buonanno and Ortenzi (). All ciliates were cultured and handled at room temperature (23 °C ± 1), and used in experiments after 1 d of starvation.…”
Section: Methodsmentioning
confidence: 99%
“…), Spirostomum ambiguum stock Pol‐5 (Buonanno et al. ), and Spirostomum teres stock Pol‐1 (Buonanno ) were grown in bacterized culture medium as described in Buonanno and Ortenzi (). All ciliates were cultured and handled at room temperature (23 °C ± 1), and used in experiments after 1 d of starvation.…”
Section: Methodsmentioning
confidence: 99%
“…Spirostomum ambiguum (approx. 1000 × 60 µm) stock Pol-5 (Buonanno & Ortenzi 2010), Spirostomum teres (approx. 380 × 40 µm) stock Pol-1 (Buonanno 2005) and Blepharisma japonicum (approx.…”
Section: Organisms and Culturesmentioning
confidence: 99%
“…Extrusomes are membrane-bound organelles that ciliates evolved in association with their cortex, and have the unique capacity to be discharged in response to a variety of environmental stimuli (Hausmann 1978). Recently, it was shown that S. sphagnetorum is "immune" to several extrusomal toxins such as stentorin from Stentor coeruleus Ehrenberg, 1830 (Buonanno 2005), climacostol from Climacostomum virens Ehrenberg, 1833 (Buonanno 2005;Buonanno et al 2008;Pucciarelli et al 2008;Buonanno & Ortenzi 2010) or blepharismin from Blepharisma japonicum Suzuki, 1954 (unpublished data) and, consequently, the predator is able to capture and ingest these ciliates. On the contrary, S. sphagnetorum is very sensitive to loxodesin(s) from Loxodes striatus Ehrenberg, 1830 (Buonanno 2005; Buonanno et al 2005) or spirostomin from Spirostomum teres Claparède et Lachmann, 1858(Buonanno 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Petrelli et al [14] have reported that climacostol can exert a potent antimicrobial activity against a panel of bacterial and fungal pathogens, including Staphylococcus, Streptococcus, Enterococcus, and Candida. Buonanno and Ortenzi [15] demonstrated that the cytotoxic potency of climacostol on free-living freshwater ciliates can be modulated by the substitution of the double bond in the aliphatic chain of the toxin with a single or a triple one. Muto et al [16,17] found that climacostol specifically inhibits respiratory chain complex I in rat liver mitochondria, inducing a consequent generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%